Agrobacterium‐mediated Genetic Transformation of Cassava. Issue 12 (12th December 2022) - Segatto, Rosana; Jones, Tira; Stretch, Danielle; Albin, Claire; Chauhan, Raj Deepika; Taylor, Nigel J.
Abstract: The storage root crop cassava ( Manihot esculenta Crantz) is predicted to remain central to future food and economic security for smallholder farming households and agricultural output in the tropics. Genetic improvement of cassava is required to meet changing farmer and consumer needs, evolving pests and diseases, and challenges presented by climate change. Transgenic and genome editing technologies offer significant potential for introducing desired traits into farmer‐preferred varieties and breeding lines, and for studying the biology of this under‐investigated crop species. A bottleneck in implementing genetic modification in this species has been access to robust methods for transformation of cassava cultivars and landraces. In this article, we provide a detailed protocol for Agrobacterium ‐mediated transformation of cassava and regeneration of genetically modified plants. Basic Protocol 1 describes how to establish and micropropagate in vitro cassava plantlets, and Alternate Protocol 1 details how to establish in vitro cultures from field or greenhouse cuttings. Basic Protocol 2 describes all steps necessary for genetic transformation in the model variety 60444, and Alternate Protocol 2 provides details for modifying this method for use with other cultivars. Finally, Basic Protocol 3 describes how to establish plants produced via Basic Protocol 2 and Alternate Protocol 2 in soil in a greenhouse. These methods have proven applications across more than a dozen genotypes and are capable of producing transgenic and gene‐edited plants for experimental purposes, for testing under greenhouse and field conditions, and for development of plants suitable for subsequent regulatory approval and product deployment. © 2022 The Authors. Current Protocols published by Wiley Periodicals LLC. Basic Protocol 1 : Establishment and propagation of in vitro cassava plantlets Alternate Protocol 1 : Establishment of in vitro plants from field or greenhouse plants Basic Protocol 2 : Genetic transformation of cassava variety 60444 Alternate Protocol 2 : Genetic transformation of additional cultivars Basic Protocol 3 : Establishment and growth of plants in the greenhouse